Editorial - Correa-Rojas, Jossue (2024)
The use of technologies has become important in different areas of life. Studies show the impact of technological development in higher education, becoming a tool that helps teaching and learning (Arellanos-Carrión, 2023; Nivela-Cornejo et al., 2021). In this regard, the Information System on Educational Trends in Latin America (SITEAL) (2022) issued a report mentioning that the region is implementing a process of integration of information and communication technologies (ICT) in the educational systems of each country, which evidences the impact of technologies in the educational sector.